Cryopreserved hepatic progenitor cells derived from human embryonic stem cells can arrest progression of liver fibrosis in rats. (24th August 2016) - Mandal, Arundhati; Raju, Sheena; Viswanathan, Chandra
Abstract: Hepatocytes generated from human embryonic stem cells (hESCs) are considered to be an excellent candidate for restoring the liver function deficiencies. We have earlier standardized a three‐step differentiation protocol to generate functional hepatocyte‐like cells (HLCs) from hESCs, which expressed the major hepatic markers. We have also found that the HLCs remain stable and functional even after extended period of in vitro culture and cryopreservation. In the present study, we have aimed to investigate the therapeutic potential of cryopreserved‐thawed hESC‐derived hepatic progenitor cells following transplantation in carbon tetrachloride‐induced fibrotic rat livers. Significant therapeutic effects, including improved hepatic histology and normal serum biochemistry of hepatic enzymes along with increased survival rate, were observed in the cell transplanted rats. This result is an encouraging indication to develop methods for clinical application of hESC‐derived hepatic lineage cells.